2001
DOI: 10.1097/00004836-200102000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative Duodenitis Accompanying Ulcerative Colitis

Abstract: Ulcerative colitis (UC) is a chronic inflammatory disease of the colon of unknown etiology. There are varied manifestations in the natural course of UC. However, duodenum is not generally considered a target organ of UC. Here, we report two patients with steroid-responsive ulcerative duodenitis with colitis that was consistent with UC, but not with Crohn's disease. We also reviewed six cases of ulcerative duodenitis with UC. Duodenal lesion with UC may be a more common phenomenon, although infrequently clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 10 publications
1
38
1
Order By: Relevance
“…In both MC and B-treated groups the protein levels were 2-fold lower than the protein levels in the luminal flora and the immune system, based mostly on the disruption of the immunoregulatory mechanisms [28][29][30] . The present study showed that a UC model, using an SH blocker and enteropathogenic E. coli, closely resembles the human situation and is reproducible with findings indicative of chronicity.…”
Section: Tnf-α Protein Expressionmentioning
confidence: 88%
See 1 more Smart Citation
“…In both MC and B-treated groups the protein levels were 2-fold lower than the protein levels in the luminal flora and the immune system, based mostly on the disruption of the immunoregulatory mechanisms [28][29][30] . The present study showed that a UC model, using an SH blocker and enteropathogenic E. coli, closely resembles the human situation and is reproducible with findings indicative of chronicity.…”
Section: Tnf-α Protein Expressionmentioning
confidence: 88%
“…The present study showed that a UC model, using an SH blocker and enteropathogenic E. coli, closely resembles the human situation and is reproducible with findings indicative of chronicity. The characteristics of the present model were colonic disease induced for nearly hundred days, the presence of clinical features such as weight loss (Figure 1), diarrhea and rectal bleeding, accompanied with macroscopic ( Figure 2) and histological alterations (Figures 3 and 4) typical of chronic ulcerative colitis in humans [16,17,29,31] . Moreover, an analysis of colonic myeloperoxidase activity [32] showed a consistent elevation of activity in the combined IA + B treatment group, indicative of severe mucosal inflammation of the descending colon ( Figure 5).…”
Section: Tnf-α Protein Expressionmentioning
confidence: 99%
“…Since Crohn's disease (CD), another IBD, can affect any portion of the digestive tract, the difference in distribution is one of the most common methods of discriminating between UC and CD; however, several cases of UC with upper gastrointestinal (GI) involvement have been reported recently. [1][2][3][4][5][6][7][8][9][10][11] The majority of such patients have duodenitis resembling UC both macroscopically and microscopically. [1][2][3] Greater spreading infl ammation such as gastroduodenitis or enteritis was also reported.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] The majority of such patients have duodenitis resembling UC both macroscopically and microscopically. [1][2][3] Greater spreading infl ammation such as gastroduodenitis or enteritis was also reported. [4][5][6] The prevalence rate of upper GI involvement is unknown, because all of these published types are case reports and there are no studies of case series in adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric and/or duodenal involvement has, rarely, been reported in association with UC. 29,30,[62][63][64][65][66] For instance, in a recent study by Lin et al, 65 esophageal, gastric and duodenal biopsies in 69 UC patients were compared with 97 non-UC controls. In that study, UC patients showed a higher prevalence rate of focal gastritis, basal mucosal mixed inflammation, superficial plasmacytosis and diffuse chronic, or chronic active, duodenitis (Figure 4).…”
Section: Uc With Crohn's-like Featuresmentioning
confidence: 99%